Early Warning Systems in the Republic of Korea: Experiences, Lessons, and Future Steps - Hyungmin Jung; Hoe Yun Jeong (Asian Development Bank (ADB), 2011)
This paper examines the cases of the Early Warning System (EWS) in the Republic of Korea, which was introduced in the wake of 1997/98 Asian financial crisis in a policy effort to prevent its recurrence. The EWS in the Republic of Korea was expanded into a national system in 2005 incorporating the finance, real estate, commodities, and labor sectors. This paper provides the descriptions of each EWS sector and documents several episodes of their policy contributions. The past experiences suggest that quantitative models tend to have difficulty predicting a crisis due to the changing nature of crises. Hence, it is desirable that quantitative models are supplemented by qualitative analysis reinforcing EWSs with various methodologies. To improve economic surveillance and message delivery to guide proper policy actions, the independence of surveillance unit should be maintained and the scope of monitoring should be expanded to incorporate regions and markets other than domestic ones given the growing influences of the external sector on the domestic economy through trade and financial linkages.
hdl:11540/2035
Keywords: E44; E61; F37; 330; EWS; crisis; surveillance; monitoring; quantitative model; qualitative analysis